2019
DOI: 10.1097/qai.0000000000001873
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: PrEPTECH: A Telehealth-Based Initiation Program for HIV Pre-exposure Prophylaxis in Young Men of Color Who Have Sex With Men. A Pilot Study of Feasibility

Abstract: Background: In the United States, young men who have sex with men (YMSM) of color represent a high number of new human immunodeficiency virus (HIV) diagnoses annually. HIV pre-exposure prophylaxis (PrEP) is effective and acceptable to YMSM of color, yet PrEP uptake is low in those communities due to barriers including stigma, cost, adherence concerns, and medical distrust. A telehealth-based approach to PrEP initiation may be a solution to those barriers. This pilot study investigates one such intervention cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
89
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 17 publications
2
89
0
3
Order By: Relevance
“…A pilot initiation program for PrEP delivery in the United States showed that teleconsultation increased access to young black MSM, as it eliminated barriers inherent in traditional clinic-based models. 11 Conversely, results from our ordinal logistic model indicate that acceptability of PrEP teleconsultation was higher among those with higher education, indicating that face-to-face consultation may not be completely replaced. Brazil faces huge social and educational disparities that may become even more profound during and after the COVID-19 pandemic.…”
mentioning
confidence: 65%
“…A pilot initiation program for PrEP delivery in the United States showed that teleconsultation increased access to young black MSM, as it eliminated barriers inherent in traditional clinic-based models. 11 Conversely, results from our ordinal logistic model indicate that acceptability of PrEP teleconsultation was higher among those with higher education, indicating that face-to-face consultation may not be completely replaced. Brazil faces huge social and educational disparities that may become even more profound during and after the COVID-19 pandemic.…”
mentioning
confidence: 65%
“…Direct-to-client telehealth (i.e., serving clients at home or in other non-healthcare settings using videoconferencing and related technology) is a well-accepted method for PrEP care that can overcome barriers related to distance, inconvenience, and stigma [ 7 , 11 13 ]. Little is known about best practices for incorporating routine laboratory monitoring in direct-to-client telehealth programs, which often serve clients who do not routinely visit healthcare settings and live far from providers.…”
Section: Introductionmentioning
confidence: 99%
“…There were no HIV seroconversions during the study. 24 In another study in the state of Iowa, pharmacists employed telemedicine to conduct patient interviews, order laboratory studies, and mail PrEP medications to patients. Study results showed that 91% of video visits resulted in PrEP initiation.…”
Section: Strategiesmentioning
confidence: 99%